Using internet primary sources to teach critical thinking skills in geography - Sharma, Martha B., 1945- (Greenwood professional guides in school librarianship., 2000)
Provides ideas and resources that will help school librarians and teachers understand the discipline of geography and locate and use Internet sites that are especially useful in helping students develop critical thinking skills in the context of geography.